Multi-Channel Optical Coherence Elastography Using Relative and Absolute Shear-Wave Time of Flight. - Eli Elyas; Alex Grimwood; Janine T Erler; Simon P Robinson; Thomas R Cox; Daniel Woods; Peter Clowes; Ramona De Luca; Franco Marinozzi; Jérémie Fromageau; Jeffrey C Bamber (PLoS ONE)
Elastography, the imaging of elastic properties of soft tissues, is well developed for macroscopic clinical imaging of soft tissues and can provide useful information about various pathological processes which is complementary to that provided by the original modality. Scaling down of this technique should ply the field of cellular biology with valuable information with regard to elastic properties of cells and their environment. This paper evaluates the potential to develop such a tool by modifying a commercial optical coherence tomography (OCT) device to measure the speed of shear waves propagating in a three-dimensional (3D) medium. A needle, embedded in the gel, was excited to vibrate along its long axis and the displacement as a function of time and distance from the needle associated with the resulting shear waves was detected using four M-mode images acquired simultaneously using a commercial four-channel swept-source OCT system. Shear-wave time of arrival (TOA) was detected by tracking the axial OCT-speckle motion using cross-correlation methods. Shear-wave speed was then calculated from inter-channel differences of TOA for a single burst (the relative TOA method) and compared with the shear-wave speed determined from positional differences of TOA for a single channel over multiple bursts (the absolute TOA method). For homogeneous gels the relative method provided shear-wave speed with acceptable precision and accuracy when judged against the expected linear dependence of shear modulus on gelatine concentration (R2 = 0.95) and ultimate resolution capabilities limited by 184μm inter-channel distance. This overall approach shows promise for its eventual provision as a research tool in cancer cell biology. Further work is required to optimize parameters such as vibration frequency, burst length and amplitude, and to assess the lateral and axial resolutions of this type of device as well as to create 3D elastograms.